2020
DOI: 10.1088/1751-8121/ab7135
|View full text |Cite
|
Sign up to set email alerts
|

Detecting non-Markovianity via uncertainty relations

Abstract: We present a formalism for detection of non-Markovianity through uncertainty relations. We show that when there is an information back-flow to the system from its environment through CP-divisibility breaking, the Choistates corresponding to the reduced system evolution contain at least one negative eigenvalue. The consequent break down of uncertainty relations for such states can be used to witness non-Markovian dynamics. We present some relevant examples of the phenomenon for qubit channels. We further prove … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…where ρ Choi is the Choi state corresponding to the system, and LB s represents the lower bound of the sum form uncertainty relation ΔA 2 + ΔB 2 ≥ LB s . Here we should mention that the uncertainty relation is calculated on the Choi state ρ Choi , and the introduction of the Choi state is presented in Appendix F. According to the discussion above, we have that the dynmics is non-Markovian when Q(A,B,ρ Choi ) < 0 65 . The evolutions of γ(t) and Q(A,B,ρ Choi ) are presented in Fig.…”
Section: Application In Non-markovianity Witnessmentioning
confidence: 94%
See 3 more Smart Citations
“…where ρ Choi is the Choi state corresponding to the system, and LB s represents the lower bound of the sum form uncertainty relation ΔA 2 + ΔB 2 ≥ LB s . Here we should mention that the uncertainty relation is calculated on the Choi state ρ Choi , and the introduction of the Choi state is presented in Appendix F. According to the discussion above, we have that the dynmics is non-Markovian when Q(A,B,ρ Choi ) < 0 65 . The evolutions of γ(t) and Q(A,B,ρ Choi ) are presented in Fig.…”
Section: Application In Non-markovianity Witnessmentioning
confidence: 94%
“…In this section, taking the dephasing channel as the illustration, we show that the uncertainty relation with more auxiliary operators can be used to witness the non-Markovian dynamics more effectively. Reference 65 showed that dynamics of a system is non-Markovian when the uncertainty relation for the Choi state corresponding to this system is violated. The uncertainty relation with tighter lower bound is violated more easily than the regular uncertainty relation, because the tighter lower bound is "closer" to the left-hand side of the uncertainty relation.…”
Section: Application In Non-markovianity Witnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the qualitative and quantitative analysis of quantum non-Markovianity is of fundamental importance in the theory of open quantum dynamics. Over the past decade, there has been numerous proposals for quantifing non-Markovianity based on CP divisibility [36,44] and non-Markovianity witness [10,36,39,40,[44][45][46][47][48][49][50][51][52][53][54][55][56]. One of the prominent non-Markovianity measures based on the composition of the dynamical map was introduced in [36], the so called RHP measure.…”
Section: Dynamics Of Non-markovianitymentioning
confidence: 99%